Therapy for fibrocystic breast disease in patients with uterine myoma - N. V. Kulagina (Опухоли женской репродуктивной системы, 2014)
Examination of 112 patients with uterine myoma revealed the high rate of concomitance of uterine and breast hyperplastic processes due to the commonness of the pathogenesis of these processes. Different forms of fibrocystic disease (FCD) were identified in 76.8% of the patients with uterine myoma; diffuse FCD with a predominance of a fibrous component was more common (54.7%). The efficacy of Indinol in the treatment of FCD was evaluated in the patients with uterine myoma. The clinical symptoms of mastodynia were relieved in 63.4% of the patients; 33.7% of the women had positive X-ray changes a year after start of therapy, as evidenced by mammography.